Answer: IF you have two equations with the 2 variables, x and y, you can substitute one y-value with the other, then solve.
Step-by-step explanation: For example:
y = 2x + 4
3x+y = 9
We can substitute the value of y from the first equation, 2x + 4, into the second equation. So, the second equaton becomes:
3x + 2x + 4 = 9
Now solve for x:
5x + 4 = 9
5x = 5
x = 1
This value of x then can be used to find y, by substituting in the value "1" for x in the first equation:
y = 2x + 4 = 2(1) + 4 = 2 + 4 = 6
So, the solution to this linear system is (1, 6)